CONCEPTUAL FRAMEWORK OF DEVELOPING STUDENTS SPEAKING SKILL BY USING VIDEO BLOGGING ACTIVITY - Yuniar, Rendhi Fatrisna (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This paper presents the idea of the integration between technology and teaching process. Taking advantage of technology in classroom like the use of video blogging will help students to make the classroom activities become more efficient since it can be used anytime and anywhere. This paper aims to show the idea of the significance of using technology, especially video blogging activity as an alternative activity to develop students’ speaking skill. The use of this medium is aimed for developing learner’s oral competence. This medium is directed to develop an effective strategy in order to perform effective communication for students through the use of peer feedback. For this objective, the medium used started with selecting the topic, giving explanation about the topic, developing the video, choosing the website, giving instructions to upload the product, and giving feedback to the result of students’ video. Digital medium makes students able to contribute actively and supportively in the speaking activities. This  conceptual paper is expected to be a reference and prior study for a researcher to conduct study related to this topic.